Clinico-Epidemiological Study of Bovine Tumours - Panchal, Jay H; Bhatt, Raghuvir H; Talekar, Shivaji H; Vadalia, Jignesh V; Padaliya, Nilesh R; Dodia, Vaibhav D (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was conducted to determine the clinico-epidemiological surveillance of bovine tumours during the period 2020-2023 based on total 11947 bovine cases registered at Veterinary Clinical Complex of the College at Junagadh (India). Among them, 3,597 (30.11%) cases had suffered with different surgical ailments and 251 cases (2.10%) were diagnosed as tumours. The highest incidence was recorded in the age group of 6 to 10 years (53.78%), followed by 11 to 15 years (27.1%), 0 to 5 years (14.34%), 16 to 20 years (4.38%) and more than 21 years (0.4%). Cases of neoplasms were observed more in females (59.36%) than in males (40.64%). Breed-wise distribution showed a higher incidence of neoplasms in Gir cattle (35.05%), followed by Kankrej cattle (27.1%), Jaffrabadi buffalo (20.32%), non-descript cattle (11.55%), non-descript buffalo (3.58%) and lowest in Holstein Friesian cattle (2.39%). The highest incidence of tumours was observed in horns (53.78 %) followed by neck (7.97%), eyes (7.57%), head region (7.57%), genitalia (7.17%), udder (5.58%), limb (4.78%), abdomen region (3.98%) and nasal cavity (1.6%).